MENINGKATKAN KINERJA KARYAWAN MELALUI GAYA KEPEMIMPINAN DEMOKRATIS DAN DISIPLIN KERJA PADA PT. LINK NET ( FIRST MEDIA Tbk ) - Regina Novalia; Wawan Prahiawan (Tirtayasa Ekonomika, 2016)
The aim of this study is to determine the effect of democratic leadership style and work discipline on employee performance. Variables used democratic leadership style (X1) and discipline (X2) on employee performance (Y).This type of research is quantitative research surveys and questionnaires, sampling technique used is sampling technique used is non-probability sampling method with types of sampling saturated or census and the number of 52 respondents. Variables used in the study is variable democratic leadership style and work discipline as an independent variable, employee performance is as dependent. The analysis method used in this research is multiple linear regression. Research data processing is done by using the tools of the program Statistical Package for the Social Sciences version 20 (SPSS).Results indicate that partially democratic leadership style positive effect but not significant, while the discipline of work have a significant effect on employee performance. And the results showed that simultaneous democratic leadership style and discipline significant influence on employee performance.Keywords : leadership, democratic leadership style, labor discipline, employee performance